Eco-friendly Synthesis of Gold Nanoparticles of Methanolic Extract of Bauhinia vahlii Leaves and Evaluation of Tyrosinase Inhibitory Activity - Panda, Pritipadma; Pal, Abhisek; Dash, Priyanka; Kar, Biswakanth; Rath, Goutam; Ghosh, Goutam (Current Enzyme Inhibition, 2025)
BackgroundThe green synthesis of gold nanoparticles (AuNPs) using natural materials has gained significant attention in recent years due to their eco-friendliness and potential applications in various fields.MethodsThe present study aimed at the green synthesis and anti-hyperpigmentation potential of gold nanoparticles (AuNPs) using a methanolic extract of Bauhinia vahlii. Furthermore, the green synthesis of the AuNPs was confirmed by UV-visible, FT-IR, XRD, and EMDEX analysis. The size and surface topological significance of green synthesized AuNPs were evaluated through Scanning Electron Microscope and Field Emission Scanning Electron Microscopy.ResultsThe size of the synthesized AuNPs was found to be in the range of 100-1000 nm. The tyrosinase inhibitory activity of AuNPs was evaluated through the mushroom tyrosinase inhibitory assay method. The tyrosinase inhibitory activities of crude extract, AuNPs, and Kojic acid were found to be 98.7 ± 0.7, 75 ± 1.3 and 41 ± 1.1 μg/ml, respectively.ConclusionHence, green synthesized AuNPs of B. vahlii leaf extract may be used as a potent anti-hyperpigmentation agent in the market of nano cosmeceuticals.
Keywords: gold nanoparticles